Model Latihan Rumanak untuk Kegiatan Ekstrakurikuler Renang Gaya Bebas Siswa Sekolah Dasar di Banggai Kepulauan: Studi Pendahuluan - Maden T Liong; Aisah R. Pomatahu; Mirdayani Pauweni (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to develop a Rumanak training model for freestyle swimming extracurricular activities as a preliminary study. The method used is research and development (R&D) up to the expert validation stage to validate the initial design of the Rumanak training model. Other data were obtained through literature studies. The results show that the Rumanak training model consists of two main components, namely basic technique training and water-based speed training. Expert validation shows that this model is feasible for use with minor improvements, particularly in the variety of water games for speed training, evaluation indicators, and training intensity adjusted to the children's abilities. The conclusion of this study is that the Rumanak training model has the potential to become a reference for more systematic, enjoyable aquatic sports learning that is in line with the developmental characteristics of elementary school children. Keywords: Extracurricular Activities, Training Model, Freestyle Swimming, Elementary School